Rethinking Vienna 1900 - Beller, Steven, 1958- (Austrian history, culture, and society ;, 2012)
Fin-de-siècle Vienna remains a central event in the birth of the century's modern culture. Our understanding of what happened in those key decades in Central Europe at the turn of the century has been shaped in the last years by an historiography presided over by Carl Schorske's Fin de Siècle Vienna and the model of the relationship between politics and culture which emerged from his work and that of his followers. Recent scholarship, however, has begun to question the main paradigm of this school, i.e. the ""failure of liberalism."" This volume reflects not only a whole range of the critiqu.